Cultural Identity and Schooling in Rural New Mexico - Arlie Woodrum (Journal of Research in Rural Education, 2009)
Following the Río Grande north from New Spain in 1540, Francisco de Coronado entered what would become New Mexico, searching for the fabled seven cities of gold. What he found instead was a poor, if hauntingly beautiful landscape where native peoples, living in cities of sophisticated pueblo design, had long ago learned to live in harmony with their often harsh, unforgiving land (Kessell, 2002; Nabokov, 2006). European colonization was slow but inevitable thereafter. Adventurers Oñate and Peralta, following in Coronado's footsteps, eventually established a colonial capital at Santa Fe in 1610. Nearly one hundred years later in 1706, a period during which the Spanish immigrant and mestizo populations had nearly succeeded in subjugating the indigenous peoples of the North, the colonial outpost of Albuquerque was founded.